The Influence of Distance Between Oil Palm Plantations and Forest Ecosystems on Spider Diversity - Ulka Sri Asih; Yaherwandi Yaherwandi; Siska Efendi (Journal of Applied Agricultural Science and Technology, 2023)
Forest conversion to oil palm plantations forms a unique agroecosystem. Forests known as a source of biodiversity are bordered by oil palm plantations with low diversity. The location of the oil palm plantation, which is directly adjacent to the forest, is thought to affect the diversity of spiders found in the agroecosystem. This study aimed to determine the effect of the distance between oil palm plantations and forests on spider diversity. The research was conducted at oil palm production centers in West Sumatra Province, Indonesia, namely Dharmasraya Regency, Pulau Punjung District, Nagari Gunung Selasih, and Sungai Kambut. In oil palm plantations, 10 sample plots (1 m x 1m) were determined along the transect line, 1 km from the forest's edge. Spiders were collected using the pitfall trap, knockdown, and hand collection methods. The spider diversity was analyzed by applying the diversity and evenness index by Shannon-Wiener. The results showed that the distance of the oil palm plantation from the forest affected the diversity of spiders. The closer the oil palm plantation is to the forest, the higher the diversity of spiders. The results of this study can be one of the considerations for oil palm business actors to maintain forests as conservation areas for organisms that provide various ecosystem services, including spiders as predators of oil palm pests.